Maintaining Local Knowledge in Folk Medicine in Mae Na Subdistrict Municipality Chiang Dao District Chiang Mai Province - Prasopsombat, Ladda (Journal of Graduate MCU KhonKaen Campus, 2022)
Local knowledge is very important. This research aims to develop local wisdom in traditional medicine. To cause inheritance and restoration of this knowledge to allow people in the community to have a proper health care system during normal times and when sick. This research is qualitative research. Use an indepth interview with the people involved. The results showed that folk medicine used social capital in the community. Folk medicine can empower the people of the community to manage, prevent and maintain the health of the people in the community and enable the community to take care of themselves in a sustainable way.